PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATERI BUMI SEBAGAI RUANG KEHIDUPAN DI KELAS X SMA NEGERI 1 DOLOK PARDAMEAN - Purba, Ayu Dearmas (Jurnal Samudra Geografi, 2025)
This research was conducted at SMA Negeri 1 Dolok Pardamean in the even semester of T.A. 2023/2024 The population in this research is class X students of SMA Negeri 1 Dolok Pardamean which consists of 5 classes, and the sample in this research consists of 2 classes, namely X-1 and Data collection techniques were used with tests. Inferential statistical quantitative data analysis technique with t-test using SPSS version 25 software The results of the hypothesis test using the independent sample T-test, obtained a significance level value of 0.000 or <0.05. So that H0 is rejected and H1 is accepted, it can be concluded that there is an influence from the application of the Problem Based Learning model on student learning outcomes regarding the Earth as a living space in class X SMA Negeri 1 Dolok Pardamean. Thus, the Problem Based Learning model can be used by teachers in schools as an alternative learning method to improve student learning outcomes.